Aktivitas Pelatihan Pengembangan Marketing pada Destinasi Ekowisata Mangrove Desa Wisata Kampung Tua Bakau Serip, Batam - Lia Fitria Anugrah; Joseph Aldo Irawan; Nevina Risha Artania; Reyhan Pramananda Hanureksa; Wisnu Bawa Tarunajaya; Herlan Suherlan; Acep Unang Rahayu; Atang Sabur Safari (Institut Teknologi dan Bisnis Semarang, 2024)
Training in a tourist village is something that many universities do in community service programs. The implementation of this program is located in the Kampung Tua Bakau Serip Tourism Village, Batam in the form of training with the theme of human resources, marketing and packaging. The method of implementing the program focuses on online material training and offline practice. This method was chosen because it can increase efficiency in terms of limited time and is able to increase opportunities for development in a short time. After the training, the participants felt very helped by this activity and got a lot of new information that would be useful for the development of the destinations they managed. This training provider does not stop at 1 university, but it is hoped that there will be new collaborations with other universities, local governments and ministries to private entrepreneurs through the CSR programs.